EFFECT OF OLIVE LEAF EXTRACT IN ADULT TWINS WITH MILD HYPERTENSION - Aydogan, C.; Schellekens, C.; Moccetti, T.; Busjahn, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Introduction: Olive leaves (Olea europaea L.) have been used in folk medicine in a variety of indications including hypertension and atherosclerosis. EFLA®943 olive leaf special extract contains the natural active ingredients of olive leaves in concentrated form. Objective: The aim of this observational study was to assess the effect of EFLA®943 as food supplement in the context of dietary measures for adults with mild hypertension. Methods: 20 adult twin pairs with blood pressure values above the optimal level (RRdiast.: 80 mmHg; RRsyst.: 120 mmHg) were enrolled, for whom a non-pharmacological therapy of the diagnosed mild hypertension was indicated. The twin pairs were divided in 2 groups. Non-medicinal measures (dietary recommendations, lifestyle change) were compared between twins to the consumption of a 500 mg EFLA®943 tablet for 8 weeks. For the statistical evaluation of this study, blood pressure, blood sugar and lipids were measured. Additionally, satisfaction and tolerance of the treatment were judged and recorded. Results: In the course of the study, both systolic and diastolic blood pressure values significantly decreased in twins treated with the olive leaf extract. The observed effect was dose-dependent. Among the measured clinical blood parameters, a significant reduction of the LDL-cholesterol values could be shown in EFLA®943-treated twins as well. The supplement was well-tolerated, no side effects were reported. Conclusions: The results of the study support the beneficial of the olive leaf special extract EFLA®943 as dietary supplement in the context of a non-pharmacological approach for the treatment of mild hypertensive states.